2014
DOI: 10.1007/s00384-013-1826-2
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival is improved in mucinous adenocarcinoma of the colon

Abstract: Histopathological evidence of mucinous adenocarcinoma in colon cancer is associated with improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…this group has recently demonstrated this potential caveat. 6 a retrospective comparative analysis comparing mucinous and nonmucinous adenocarcinoma of the colon alone demonstrated an independent association between mucinous and improved overall survival contrary to the findings of studies combining CC and RC. Consequently, the role of lVi+ in oncological outcomes is yet to be separately established in CC and RC, 23,24 OBJECTIVE this study aims to separately evaluate the role of lVi+ in CC and RC with respect to overall survival (os), disease-free survival (Dfs), and locoregional and systemic recurrence.…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…this group has recently demonstrated this potential caveat. 6 a retrospective comparative analysis comparing mucinous and nonmucinous adenocarcinoma of the colon alone demonstrated an independent association between mucinous and improved overall survival contrary to the findings of studies combining CC and RC. Consequently, the role of lVi+ in oncological outcomes is yet to be separately established in CC and RC, 23,24 OBJECTIVE this study aims to separately evaluate the role of lVi+ in CC and RC with respect to overall survival (os), disease-free survival (Dfs), and locoregional and systemic recurrence.…”
contrasting
confidence: 63%
“…[1][2][3][4][5] however, 20% of node-negative patients develop disease recurrence, hence, the importance of additional prognostic parameters in distinguishing high-and low-risk patients. [6][7][8][9] lymphovascular invasion (lVi) (characterized by the extension of tumor cells into lymphatic and/or blood vessels) is used as an adjunct to tnm staging in stage ii CRC. lymphovascular invasion positivity (lVi+) is a critical prognostic indicator and, as such, is documented in over 90% of histopathology reports.…”
mentioning
confidence: 99%
“…However, some studies have reported a lower survival rate in patients with a MCC [152224]. Surprisingly, Hogan et al [28] showed an improved survival in patients with a mucinous carcinoma of the colon. These discrepancies may reflect heterogeneity in the population of patients, lack of stratification by stage, exclusion of rectal primary tumors in some studies, and different numbers of patients accrued.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis from the National Cancer Database showed inferior OS in MA of the rectum but not of the colon [9]. Interestingly, Hogan et al reported an improved survival in patients with MA [25].…”
Section: Discussionmentioning
confidence: 99%